2021
DOI: 10.15585/mmwr.mm7014e1
|View full text |Cite|
|
Sign up to set email alerts
|

Provisional Mortality Data — United States, 2020

Abstract: On March 31, 2021, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr).CDC's National Vital Statistics System (NVSS) collects and reports annual mortality statistics using data from U.S. death certificates. Because of the time needed to investigate certain causes of death and to process and review data, final annual mortality data for a given year are typically released 11 months after the end of the calendar year. Daily totals reported by CDC COVID-19 case surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
222
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 256 publications
(248 citation statements)
references
References 1 publication
4
222
0
1
Order By: Relevance
“…This is why we also performed comparisons in selected age groups in order to identify the ages primarily affected by changes in mortality. Ahmad et al [ 5 ], using a similar method based on standardized and age-specific mortality rates, found for the United States a 15.9% increase of the standardized mortality rate in 2020 compared to 2019, an excess mortality almost twice as large as our estimation for Switzerland. However, they also reported mortality rates that increased sharply with age and were higher in men than in women.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This is why we also performed comparisons in selected age groups in order to identify the ages primarily affected by changes in mortality. Ahmad et al [ 5 ], using a similar method based on standardized and age-specific mortality rates, found for the United States a 15.9% increase of the standardized mortality rate in 2020 compared to 2019, an excess mortality almost twice as large as our estimation for Switzerland. However, they also reported mortality rates that increased sharply with age and were higher in men than in women.…”
Section: Discussionsupporting
confidence: 67%
“…This is why we also performed comparisons in selected age groups in order to identify the ages primarily affected by changes in mortality. Ahmad et al [5], using a similar method based on standardized and age-specific mortality…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report found that age-adjusted COVID-19 death rates in 2020 were highest among non-Hispanic AI/AN (187.8 deaths per 100,000), followed by Hispanic (164.3), non-Hispanic Black (151.1), Non-Hispanic NHOPI (122.3), non-Hispanic White (72.5), non-Hispanic Asian (66.7), and non-Hispanic Multiracial (31.8) populations. 9 Prior analyses have found that COVID-19 death rates increase with age within each racial/ethnic group, and that death rates are highest among those 85 years and older. 1 …”
Section: Discussionmentioning
confidence: 99%
“…The total drug overdose deaths jumped to over 85,000 in the 12 months ending in August 2020, which shows a 20% increase in drug overdose deaths than in 2019. The number of drug overdose-involved deaths equals over 20% of the total number of COVID-19 deaths (377,883) in the United States in 2020 (3)(4)(5). Two main strategies have been utilized to combat opioid overdoses so far, including (i) abuse-deterrent formulations (ADFs) and (ii) antagonist-based formulations or devices (6).…”
Section: Introductionmentioning
confidence: 99%